Marital relationship, parenting practices, and social skills development in preschool children - Rikuya Hosokawa; Toshiki Katsura (BMC, 2017)
Abstract Background This study examined the pathways by which destructive and constructive marital conflict leading to social skills development in preschool children, are mediated through negative and positive parenting practices. Methods Mothers of 2931 Japanese children, aged 5-6 years, completed self-report questionnaires regarding their marital relationship (the Quality of co-parental communication scale) and parental practices (the Alabama parenting questionnaire). The children's teachers evaluated their social skills using the Social skills scale. Results Path analyses revealed significant direct paths from destructive marital conflict to negative parenting practices and lower scores on the self-control component of social skills. In addition, negative parenting practices mediated the relationship between destructive marital conflict and lower scores on cooperation, self-control, and assertion. Our analyses also revealed significant direct paths from constructive marital conflict to positive parenting practices, and higher scores on cooperation and assertion. Positive parenting practices mediated the relationship between constructive marital conflict and higher scores on self-control and assertion. Conclusions These findings suggest that destructive and constructive marital conflict may directly and indirectly influence children's social skills development through the mediation of parenting practices.